Analiza in primerjava pristopov pri gradnji podatkovnih skladišč - Golob, Izidor (Uporabna informatika (Ljubljana), 2003)
Data warehousing along with its structures and processes, is designed to support the business process. A data warehouse, containing data, cleansed and integrated in the data migration process, gives an integrated view on the enterprise's business data. In this paper three basic approaches to building data warehouse are analyzed and compared. Depending on the approach chosen, the result is centralized, distributed or federated data warehouse architecture. The results show that there is a fundamental difference among the presented approaches due to differences in concepts, data model s and methodology used. Based on the results, a method for determining an optimal approach to building data warehouse for given enterprise is given. In general, the perfect approach does not exist as each one has its own strengths and weaknesses.
Keywords: analiza; arhitektura (računalnik); podatki; podatkovna skladišča